2013
DOI: 10.1155/2013/249615
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressing Osteomyelitis of the Mandible

Abstract: Acute osteomyelitis exists as a refractory disease even now, which usually exhibits systemic symptoms such as fever or malaise and local redness or swelling. The present paper describes a case of acute osteomyelitis of the mandible that was rapidly progressing without typical symptoms. The patient had liver cirrhosis, which should be one of the systemic factors that affect immune surveillance and metabolism. Actinomycotic druses and filaments were detected from the sequestrum. These were considered to play a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
2
0
6
Order By: Relevance
“…The presence of liver cirrhosis in human beings has been shown to be associated with development of osteomyelitis (Morrison and Naktin 2009, Akiyama and others 2013, Kusuyama and others 2013, Jeong and others 2014). One epidemiological study showed that the presence of liver cirrhosis resulted in an increased risk of development of vertebral osteomyelitis (odds ratio of 2.6) (Akiyama and others 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of liver cirrhosis in human beings has been shown to be associated with development of osteomyelitis (Morrison and Naktin 2009, Akiyama and others 2013, Kusuyama and others 2013, Jeong and others 2014). One epidemiological study showed that the presence of liver cirrhosis resulted in an increased risk of development of vertebral osteomyelitis (odds ratio of 2.6) (Akiyama and others 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycosis is shown clinically like tuberculosis and granuloma mimicking malignant lesion. Actinomycotic osteomyelitis usually proceeds slowly, but there were severe cases that infection invaded to mid-face, skull base, and cranium [15], and that proceed so rapidly that mandible was fractured, requiring reconstruction in immunosuppressive patient [16]. It is very important to diagnose actinomycosis, but it is reported that usual bacterial examination can confirm actinomycosis in less than 50% and first visit examination in less than 10% [17].…”
Section: Pathophysiology Of Actinomycotic Osteomyelitis Has Notmentioning
confidence: 99%
“…La etiopatogenia es multifactorial, siendo la principal causa la infección por un foco bacteriano, microorganismos (Gram positivos, Gram negativos) y a veces presencia fúngica(1, 3,4). Otras causas que contribuyen al desarrollo de la patología son los traumas, fracturas, enfermedades odontogénicas infecciosas, ciertos fármacos y la radioterapia (4,5).…”
Section: Introductionunclassified
“…Existen varios sistemas de clasificación de la osteomielitis, siendo la más aceptada, la que se determina de acuerdo a la duración; aguda, crónica, reflejándose de diferentes formas y características tanto en la clínica como en las imágenes diagnósticas, que causa confusión en el clínico y radiólogo (3,(7)(8)(9)12). El diagnóstico diferencial de la osteomielitis incluye infecciones, tumores óseos benignos, neoplasias malignas, trastornos metabólicos, traumatismos y osteonecrosis (4,12,13).…”
Section: Introductionunclassified
See 1 more Smart Citation